(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The largest policies that are effective in the housing sector are "land management" policies, which express the distribution of missions throughout the country and, consequently, the distribution of population. These policies have been adopted at the macro level of the country and as an upstream policy, have a great impact on the housing sector. Marginalization problems around metropolitan areas are rooted in land management throughout the country. Establishing a real estate information system can be an effective aid to planning and implementing land management policies. Comprehensive cadaster or cadaster with dual military application that in addition to fulfilling the objectives of the definition of cadaster in a specific sense, meet the needs of other socio-economic development programs in which the division of land and their use are considered. On the other hand, government planning in the land and housing market in order to implement policies in the field of real estate, including housing, agriculture, industry and services requires transparent information in this market. In fact, governments need to organize and organize information in the land and housing market. Accordingly, the purpose of this study is to review the findings regarding the achievement of a comprehensive cadastral system. In this regard, advanced cadastral imagery, cadastral objectives, the need to implement the cadastral plan, explain the cadastral implementation strategy of the country, various operational steps to prepare a cadastral map and smart real estate identity card were studied descriptively.